Transmission of definite/indefinite meaning through context in Kazakh linguistics - Azharbekova, E.N. (KSU Publ., 2017)
This article considered ways of transfer of definite/indefinite meanings in Russian, Turkic linguistics. The author of article proves definite/indefinite category inherent in the Russian linguistics as well as Turkic leaning on researches of turcologists. It is proved that, definite/indefinite is transmitted through articles in Greek- Romance languages, and in Russian through a word order and phrase intonations, the genitive and accusative case, a type of categories, from this, it is explained that in Turkic languages there is no definite/indefinite article, but there is a meaning of definite/indefinite which is transmitted through other ways. By means of exact examples the author specifies that, definite/indefinite value is transferred through context in Kazakh.
Қазақ тіл білімінде белгілілік/белгісіздік мəннің контекст арқылы берілуі
Передача в казахском языкознании значения определенности/неопределенности посредством контекста
Keywords: context; definiteness; indefiniteness; Turkic linguistics; Russian linguistics; word order; phrase intonation; genitive and accusative cases; demonstrative pronoun; indefinite pronoun; incomplete sentence